The synergistic effects of humic acid, chitosan and Bacillus subtilis on tomato growth and against plant diseases - Qiu, Cunpu; Bao, Ying; Lü, Dingding; Yan, Mengyuan; Li, Guilong; Liu, Kai; Wei, Shiping; Wu, Meng; Li, Zhongpei (Frontiers in Microbiology, 2025)
Understanding the effects of bio-antimicrobial materials on plant growth and against diseases and the relevant mechanisms are highly important for sustainable soil use and plant safety production. This study explored the impacts and corresponding mechanisms of the combined utilization of humic acid, chitosan, and Bacillus subtilis (B. subtilis) on tomato growth and diseases occurrence through a greenhouse pot experiment. The plant height, fresh weight, disease index, rhizosphere microbial community, and root exudates composition of tomatoes were determined. With the combined application of humic acid, chitosan and B. subtilis (HBC), the height and fresh weight of tomato plants were significantly increased (p < 0.05), and the incidence of plant diseases was decreased by 45.1%. In HBC treatment, the diversity of fungal and bacterial communities was notably enhanced. The relative abundances of Bacillus, Gemmatimonas, Neobacillus, Acinetobacter, Humicola increased, while the relative abundances of Sphingomonas, especially soil-borne plant pathogen Fusarium and Ralstonia, significantly decreased (p < 0.05). Besides the increased diversity of root exudates, the content of phenolic acids, which are allelochemicals related to continuous cropping disorder, decreased. The results of cooccurrence network analysis indicated that the abundances of Eicosanoids, Fatty acids and conjugates, and Flavonoid lycosides compounds in root exudates, which are positively correlated with pathogenic bacteria, decreased in HBC treatment. Results indicated HBC’s synergistic effect on tomato growth and disease resistance is related to its regulation of microbial community and root exudates. The study results promote the development of biological control technology and highlight its promising application in plant safety production.